Heterogeneity of Antibiotics Multidrug-Resistance Profile of Uropathogens in Romanian Population - Petca, Răzvan-Cosmin (Antibiotics (Basel), 2021)
Urinary tract infections (UTIs) are a leading cause of morbidity for both males and females. The overconsumption of antibiotics in general medicine, veterinary, or agriculture has led to a spike in drug-resistant microorganisms; obtaining standardized results is imposed by standard definitions for various categories of drug-resistant bacteria—such as multiple-drug resistant (MDR), extensive drug-resistant (XDR), and pan drug-resistant (PDR). This retrospective study conducted in three university teaching hospitals in Romania has analyzed urine probes from 15,231 patients, of which 698 (4.58%) presented multidrug-resistant strains. Escherichia coli was the leading uropathogen 283 (40.54%), presenting the highest resistance to quinolones (R = 72.08%) and penicillin (R = 66.78%) with the most important patterns of resistance for penicillin, sulfonamides, and quinolones (12.01%) and aminoglycosides, aztreonam, cephalosporins, and quinolones (9.89%). Klebsiella spp. followed—260 (37.24%) with the highest resistance to amoxicillin-clavulanate (R = 94.61%) and cephalosporins (R = 94.23%); the leading patterns were observed for aminoglycosides, aminopenicillins + β-lactams inhibitor, sulfonamides, and cephalosporins (12.69%) and aminoglycosides, aztreonam, cephalosporins, quinolones (9.23%). The insufficient research of MDR strains on the Romanian population is promoting these findings as an important tool for any clinician treating MDR-UTIs.